منهج التزكية الذاتية وأثره في تعزيز الصحة النفسية لدى عينة من ربات البيوت - صوفية، فضيلة محمد (الجامعة الأسمرية الإسلامية - كلية التربية زليتن, 2024)
هدف البحث إلى تبيين مقاصد التزكية الذاتية، وأثرها في تعزيز الصحة النفسية، التي يسعى إليها كل إنسان، ليحيا حياة طيبة، خالية من العوائق والأزمات النفسية، محاولا معالجة الأسباب المذهبة للسواء النفسي، للتوسم بالاطمئنان النفسي، وحيث إن التزكية مصطلح قرآني، فقد اعتمدنا الشواهد القرآنية، وتحليلها نظريا ضمن أدبيات البحث، وتطبيقها إجرائيا، على عينة البحث، لقياس التوازن النفسي، بالاعتماد على المنهج التجريبي، ذو المجموعتين: الضابطة والتجريبية، بعينة مقدارها (30) مفردة من المجتمع الأصلي للبحث (ربات البيوت)، وذلك لقياس الأثر المستهدف، عن طريق مقياس (الصحة النفسية) ذو (ثلاثة أبعاد)، ومكون من (45) عبارة، وبنظام سلمين (نعم، لا) لدقة الإجابة، وذو التطبيقين (القبلي والبعدي)، وتطلب المنهج تطبيق تقنيات تدريسية وعظية تكونت من (17) محاضرة استمرت (36) يوما، وختم البرنامج التطبيقي، بالقياس البعدي، وعولجت إجاباته إحصائيا ببرنامج (spss) فكانت النتائج: للتطبيق القبلي أن نسب المجموعتين شبه متساوية ولا يوجد فرق جوهري بينهما، وثبت وجود فروق دالة إحصائيا عند مستوى (α ≤ 0.05) بين الضابطة والتجريبية على التطبيق البعدي لصالح التجريبية، وهو ما يثبت وجود أثر فاعل للتزكية الذاتية، وضبط النفس ذاتيا، للوصول إلى التمتع بالصحة النفسية، واستقرارها بعد فترة زمنية (قياس المتابعة)، الذي أفاد باستقرار نسبة ثبات النتائج الواردة منه، حيث أظهرت مقدار (34.6)، بما يناظره في الاختبار البعدي للتجريبية (35.0)، وهو ما يعني فاعلية البرنامج ومضمونه، في نفوس العينة عن تبصر وإدراك ذاتي مما يوحي بإمكانية تطبيقه في المؤسسات التربوية ومراكز التأهيل لأجل صحة نفسية سوية، استنادا لقوله تعالى: ﴿ بَلِ ٱلۡإِنسَٰنُ عَلَىٰ نَفۡسِهِۦ بَصِيرَةٞ ١٤﴾ (القيامة: 14) The aim of the research is to clarify the purposes of self-purification, and its impact on promoting psychological health, which every person seeks, in order to live a good life, free of obstacles and psychological crises, trying to address the underlying causes of psychological well-being, to describe psychological reassurance, and since purification is a Qur’anic term, we have adopted the evidence. The Qur’an, and analyze it theoretically within the research literature, and apply it procedurally, on the research sample, to measure psychological balance, based on the experimental method, with two groups: control and experimental, with a sample of (30) individuals, from the original population of the research (housewives), in order to measure the targeted effect. Through a (mental health) scale with (three dimensions), consisting of (45) statements, and with a two-scale system (yes, no) for accuracy of the answer, and with two applications (pre and post), the curriculum required the application of pedagogical teaching techniques, which consisted of (17) lectures. It lasted (36) days, and the applied program was concluded with the post measurement, and his answers were treated statistically with the (SPSS) program. The results were: For the pre-application the proportions of the two groups are almost equal and there is no fundamental difference between them, and it was proven that there are statistically significant differences at the level (α ≤ 0.05) between the control and the experimental group. On the post-application in favor of the experimental, which proves the existence of an effective effect of self-recommendation and self control, to achieve the enjoyment of mental health and its stability after a period of time (follow-up measurement), which reported the stability of the stability rate of the results received from it, as it showed an amount of (34.6), What corresponds to it in the experimental post-test (35.0), which means the effectiveness of the program and its content, in the souls of the sample with insight and self-awareness, which suggests the possibility of its application in educational institutions and rehabilitation centers for healthy mental health, Resurrection (القيامة: 14) (بَلِ ٱلۡإِنسَٰنُ عَلَىٰ نَفۡسِهِۦ بَصِيرَةٞ ١٤) based on the Almighty’s saying.
Keywords: القرآن الكريم -- الإرشاد النفسي -- النفس البشرية -- التوازن النفسي